Raylan - Leonard, Elmore, 1925- (New York : William Morrow, 2012)
When Federal Marshall Raylan Givens squares off against a known offender, he will warn the man, "If I have to pull my gun I'll shoot to kill." Except this time he finds the offender naked in a bathtub, doped up and missing his kidneys. Raylan knows there's big money in body parts, but by the time he finds out who is making the cuts, he is lying naked in a bathtub himself.
Keywords: United States marshals -- Fiction; Sale of organs, tissues, etc. -- Fiction; Black market -- Fiction; Harlan County (Ky.) -- Fiction; Suspense fiction